The outcomes of patients with septic shock treated with propafenone compared to amiodarone for supraventricular arrhythmias are related to end-systolic left atrial volume - Waldauf, Petr; Porizka, Michal; Horejsek, Jan; Otahal, Michal; Svobodova, Eva; Jurisinova, Ivana; Maly, Michal; Brozek, Tomas; Rulisek, Jan; Trachta, Pavel; Tencer, Tomas; Krajcova, Adela; et al. (European heart journal. Acute cardiovascular care, 2024)
AIMS: A recently published trial has shown no differences in outcomes between patients with new-onset supraventricular arrhythmia (SVA) in septic shock treated with either propafenone or amiodarone. However, these outcome data have not been evaluated in relation to the presence or absence of a dilated left atrium (LA). METHODS AND RESULTS: Patients with SVA and a left ventricular ejection fraction ≥ 35% were randomized to receive intravenous propafenone (70 mg bolus followed by 400-840 mg/24 h) or amiodarone (300 mg bolus followed by 600-1800 mg/24 h). They were divided into groups based on whether their end-systolic left atrial volume (LAVI) was ≥40 mL/m². The subgroup outcomes assessed were survival at ICU discharge, 1 month, 3 months, 6 months, and 12 months. Propafenone cardioverted earlier (P = 0.009) and with fewer recurrences (P = 0.001) in the patients without LA enlargement (n = 133). Patients with LAVI < 40 mL/m2 demonstrated a mortality benefit of propafenone over the follow-up of 1 year [Cox regression, hazard ratio (HR) 0.6 (95% CI 0.4; 0.9), P = 0.014]. Patients with dilated LA (n = 37) achieved rhythm control earlier in amiodarone (P = 0.05) with similar rates of recurrences (P = 0.5) compared to propafenone. The outcomes for patients with LAVI ≥ 40 mL/m2 were less favourable with propafenone compared to amiodarone at 1 month [HR 3.6 (95% CI 1.03; 12.5), P = 0.045]; however, it did not reach statistical significance at 1 year [HR 1.9 (95% CI 0.8; 4.4), P = 0.138]. CONCLUSION: Patients with non-dilated LA who achieved rhythm control with propafenone in the setting of septic shock had better short-term and long-term outcomes than those treated with amiodarone, which seemed to be more effective in patients with LAVI ≥ 40 mL/m². TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT03029169, registered on 24 January 2017.
Keywords: propafenon; tepový objem; Septic shock; Propafenone; Humans; Stroke Volume; lidé středního věku; Amiodarone; Female; Aged; Tachycardia, Supraventricular; výsledek terapie; Cardioversion; Supraventricular arrhythmia; senioři; lidé; supraventrikulární tachykardie; septický šok; Heart Atria; Shock, Septic; ženské pohlaví; Male; Middle Aged; Treatment Outcome; antiarytmika; srdeční síně; Anti-Arrhythmia Agents; mužské pohlaví; Atrial fibrillation; amiodaron